Global Research Trends on COVID-19: A Bibliometric Analysis: Communicating the global research trends - Pahlevan Sharif, Saeed; Waheed, Hassam; Naghavi, Navaz; Goudarzian, Amir Hossein; Sharif Nia, Hamid (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: The emergence of the human coronavirus (SARS-CoV-2) in December 2019 caused a public health crisis. Knowing the progress of studies in the field of COVID-19 helps researchers a lot in summarizing the available information. Using a bibliometric analysis this study aims to assess the characteristics of the research publications involving COVID-19 globally. Methods: To make the bibliometric indicators non-exhaustive, a bibliometric database is created where researchers can have immediate access and contribute to COVID-19 related bibliometric indicators. PubMed database was searched for COVID-19 publications published within 1st January up until 13th March 2020. An R package of Bibliometrix and VOSviewer for comprehensive science mapping analysis and visualization are utilized. Analysis parameters include publication type, pattern of international collaboration, leading journals, the most cited papers and the most productive countries. A total of 786 COVID-19 publications in 238 journals from 69 countries indicates the international spread of the research within short period. Results: The Lancet (7.64%), Journal of Medical Virology (7.11%) and BMJ (6.08%) had the largest share of publications respectively. Manuscripts published in The New England Journal of Medicine (15 citations), Nature (10 citations), and The Lancet (10 citations) have received the highest citations. China was the largest contributor with 44.27% of total publications followed by the United States (4.58%) and Italy (2.67%). Conclusions: Canada, Germany and United States had the greatest proportion of international research collaboration as per multiple country publication ratio. There is rapid increase in research activities related to COVID-19 in the initial 11 weeks of 2020.